(untitled) (Philology, 2021)
The article discusses three functional-linguistic categories: temporality, causality, and affectuality, that are analyzed through the theoretical formulations and methodology of the structural-functional approach in linguistics. The results are based on research, conducted in the last twenty years covering French and international scholarly projects, dissertations, and diploma papers, carried out under my scholarly guidance. All these exhibit the close ties and relationships between language forms, their meaning and usage, in French: forms, sens, and usages.